Educating planners in Europe: A review of 21st century study programmes - Frank, Andrea I.; Mironowicz, Izabela; Lourenço, Julia; Franchini, Teresa; Ache, Peter; Finka, Maroš; Scholl, Bernd; Grams, Anita (Progress in planning, 2014)
•218 institutions in 47 member states of the Council of Europe offer planning education.•European integration policies are influencing planning practice and curricula.•Different educational models for planning education co-exist throughout Europe.•Re-structuring of degrees post Bologna impacts on provision of education models.•Many professional associations consider Bachelor insufficient for planning practice. Education for urban, regional and spatial planning has become a regular subject throughout most European nations; this can be attributed in part to European policies promoting planning and spatially balanced development, but also to the recognition that planning can support sustainability. Nevertheless, there is lingering and justifiable concern about the status, profile and recognition of planning as a profession in its own right with the result that planning and planning education remain contested territories in academia. Conceptions of planning differ between countries and over time. The array of different planning cultures and associated educational models and pedagogies that traditionally have coexisted in Europe mean that education for planning can be either very visible or leading a shadow existence being embedded in programmes of other disciplines. While planning education provision customarily has been shaped by changes in planning practice paradigms and the profession, in 21st century Europe the provision is also influenced by European integration policies, the Bologna process and powerful transformations affecting the higher education sector writ large. This review seeks to advance our understanding of the complex dynamics at work, which to date have been only partially explored in the literature, by taking stock of the current state-of-play of planning education provision in Europe. Aside from examining the factors influencing planning education in Europe, an inventory of planning education programmes available throughout the member states of the Council of Europe was developed to quantify the provision as a critical first step. Figures indicate a substantial increase in the number of programmes when compared to limited historical data. Data also suggest an underdeveloped provision for education in planning in about ten per cent of European countries. Country case studies with historically differing planning cultures and education provision, i.e., Spain, Portugal, Finland, Poland, Slovakia, the United Kingdom and Switzerland are used to compare and explore trends and developments (e.g., in respect to programme structure, curriculum content and focus, professional conceptions, specialisms) in detail. Findings demonstrate, both, an enduring power of national preferences and traditions but also some emerging commonalities. Overall a picture of increasing pluralism and diversity of education models transpires in the aftermath of Bologna which may contravene efforts to establish cross-national professional recognition and standards. Education for planning seems to embrace trends to provide increasingly international learning experiences and degrees while the provision of flexible recognised (online) degree programmes remains sparse. Recommendations for future actions and strategies to further develop and strengthen the field which is at present complex and little coordinated conclude the contribution.